(untitled) (Nigerian Journal of Technology, 2018)
This paper examines the Sombriero River with a view of ascertain its discharge rate, potential hydro power can be derived and to provide a RETScreen-based financial viability analysis of adopting the river for a Micro Hydro Power Scheme. The river discharge was measured via the “Float Method Technique” while the river surface and mean velocities, derivable power as well as the scheme’s viability were computed. The Sombriero river has the capacity to deliver 51kW power, it would be a viable venture at a tariff price of 127.61/MWh and would be most suitable for Run-Off-River hydro scheme considering that it has low water head and substantial discharge. http://dx.doi.org/10.4314/njt.v37i2.19